2011
DOI: 10.1007/s10826-011-9444-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Child and Family Team Composition on Wraparound Fidelity: Examining Links Between Team Attendance Consistency and Functioning

Abstract: Wraparound, the process by which families and professionals work in collaboration to help plan and implement services, has become the dominant practice model for providing services for children with severe emotional disturbances and their families (Faw 1999), particularly within Systems of Care (SOCs;Hernandez 2003;Stroul and Friedman 1986). The wraparound model consists of ten principles, including a team-based model for planning and implementation of services (Suter and Bruns 2009). These child and family te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Conversely, McCrae and Fusco (2010) reported more challenges for children in out-of-home care because parents were more confronted with their individual problems that prevent their engagement (e.g., substance abuse and mental health issues). Finally, some studies have noted that it is difficult to include key players in forming a team and developing trustful relationships between team members if the team members are changed frequently and do not participate regularly in the meetings (Munsell et al, 2011;Walker & Schutte, 2004). Landsman, Boel-Studt, and Malone (2014) also showed that active search and engagement with extended families through a family finding project was helpful for facilitating effective teamwork by enhancing longterm and stable connections with valuable adults.…”
Section: Case Characteristics and Teamworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, McCrae and Fusco (2010) reported more challenges for children in out-of-home care because parents were more confronted with their individual problems that prevent their engagement (e.g., substance abuse and mental health issues). Finally, some studies have noted that it is difficult to include key players in forming a team and developing trustful relationships between team members if the team members are changed frequently and do not participate regularly in the meetings (Munsell et al, 2011;Walker & Schutte, 2004). Landsman, Boel-Studt, and Malone (2014) also showed that active search and engagement with extended families through a family finding project was helpful for facilitating effective teamwork by enhancing longterm and stable connections with valuable adults.…”
Section: Case Characteristics and Teamworkmentioning
confidence: 99%
“…Other studies have identified significant factors for promoting either team formation/composition or team functioning/cohesion (Kemp et al, 2009;McCrae & Fusco, 2010). Other studies have also examined the relationship between the structural and functional aspects of teamwork as a team process (Munsell et al, 2011;Parcel & Pennell, 2012). Despite the growing interest in building effective teamwork, few empirical studies have identified significant factors affecting teamwork in family meetings within child welfare settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While a significant literature has identified issues in the implementation of SOCs (e.g., Center for Mental Health Services 2003; Cook and Kilmer 2004;Holden et al 2003;Kilmer et al 2010b;Kutash et al 2011;Lunn et al 2011;Pandiani et al 1996) and wraparound (e.g., Bertram et al 2011;Bruns et al 2011;Cook et al 2007;Epstein et al 2003;Palamaro Munsell et al 2011;Walker et al 2003;Walker and Schutte 2005), including a Special Issue (Bruns and Walker 2011a) focusing on wraparound services and wraparound implementation, there is scant knowledge regarding the particular elements of wraparound, or the specific characteristics of SOCs, that contribute to more positive outcomes for children and their families.…”
mentioning
confidence: 99%
“…Many assessments of wraparound fidelity involve team member interviews regarding team functioning over a period of time (e.g., 3 months); however, assessments of the processes occurring at team meetings have been found to be important indicators of wraparound implementation (e.g., Haber et al 2012;Palamaro Munsell et al 2011) that have also been found to relate to better child outcomes (e.g., Haber et al 2010;Hemphill et al 2010). Given increasing use of wraparound to address a wide range of problems experienced by children and families Bruns and Walker 2011b), better understanding of the systemic factors that lead to better wraparound fidelity and more positive outcomes is imperative.…”
mentioning
confidence: 99%